2008
DOI: 10.1111/j.1600-0463.2008.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation in promoter regions of cyclin‐dependent kinase inhibitor genes in adenoid cystic carcinoma of the salivary gland

Abstract: Adenoid cystic carcinoma (ACC) is a common malignant neoplasm of the salivary gland. The mechanism underlying ACC carcinogenesis is not fully elucidated, although data on associated genetic alterations are accumulating. Cyclin-dependent kinase inhibitors (CKIs) act as tumor suppressors in various cancers, and aberrant methylation in the CKI gene promoter region has been linked to gene silencing and downregulation of expression. The present study investigated methylation of CKI genes, p15, p18, p19, p21, and p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…CKIs, as tumor suppressors, are responsible for the modulation of the activity of Cdk/cyclin complexes [35]. And the aberrant methylation such as PRC2-mediated histone methylation in the CKI gene promoter region is associated with gene expression suppression [36-39]. Additionally, plenty of lncRNAs have been reported to modulate specific genetic loci through recruiting PRC2 and PRC2-mediated epigenetic regulation play important role in tumorigenesis [17, 30, 31, 40-42].…”
Section: Discussionmentioning
confidence: 99%
“…CKIs, as tumor suppressors, are responsible for the modulation of the activity of Cdk/cyclin complexes [35]. And the aberrant methylation such as PRC2-mediated histone methylation in the CKI gene promoter region is associated with gene expression suppression [36-39]. Additionally, plenty of lncRNAs have been reported to modulate specific genetic loci through recruiting PRC2 and PRC2-mediated epigenetic regulation play important role in tumorigenesis [17, 30, 31, 40-42].…”
Section: Discussionmentioning
confidence: 99%
“…14-3-3 σ negatively regulates the cell cycle by binding to cyclin/CDK complexes and inhibiting their interactions, thereby preventing cell cycle progression (124) . It has been shown to be required for stable G2 cell cycle arrest and also for activating p53 after DNA damage (125) . 14-3-3 σ is silenced via promoter methylation in many types of tumors (125) .…”
Section: Dna Methylation In Accmentioning
confidence: 99%
“…It has been shown to be required for stable G2 cell cycle arrest and also for activating p53 after DNA damage (125) . 14-3-3 σ is silenced via promoter methylation in many types of tumors (125) . In ACC Uchida et al (118) reported promoter methylation of 14-3-3 σ in 8 out of 14 tumors and demonstrated that the aberrant methylation was in fact responsible for decreased gene expression.…”
Section: Dna Methylation In Accmentioning
confidence: 99%
See 1 more Smart Citation
“…These methylation changes can result in aberrant activation of oncogenes (by hypomethylation) or silencing of tumor suppressor genes (by hypermethylation). Several methylation-regulated, ACC-associated candidate genes have been identified, including PTEN [4], cyclin-dependent kinase inhibitors [5], RASSF1 , RARbeta2 [6] p16 INK4a , DAPK [7], 14-3-3 sigma [8], E-cadherin [9], and AQP1 [10]. Since DNA methylation and transcription regulation are frequent events in human cancers, our group has developed epigenomic screening methods to search for novel hypomethylated oncogene candidates in various types of human cancers, including salivary gland ACC [10].…”
Section: Introductionmentioning
confidence: 99%